2018
DOI: 10.1016/j.jamcollsurg.2018.01.049
|View full text |Cite
|
Sign up to set email alerts
|

Same-Day Discharge after Laparoscopic Roux-en-Y Gastric Bypass: An Analysis of the Metabolic and Bariatric Surgery Accreditation and Quality Improvement Program Database

Abstract: Same-day discharge after LRYGB is associated with increased morbidity and mortality compared with POD1 discharge. The practice of same-day discharge after LRYGB should be considered experimental until further studies confirm which patient characteristics will ensure safe same-day discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 19 publications
(15 reference statements)
1
23
2
Order By: Relevance
“…For instance, Rebibo et al reported a cohort with a 40% increase in the readmission rate (from 4% to 5.6%) [23] and others observed an increase in the ER visit rate [24]. Using the Metabolic and Bariatric Surgery Accreditation and Quality Improvement Program data set, Inaba et al found a signi cantly higher morbidity (3.76% vs. 1.54%) and mortality rate (0.94% vs. 0.05%) when comparing same-day discharge to POD1 discharge [25]. Similarly, Morton et al discovered that an LOS of ≤1 day was associated with a signi cantly increased risk of 30-day mortality (OR 2.02) for RYGB patients [26].…”
Section: Discussionmentioning
confidence: 98%
“…For instance, Rebibo et al reported a cohort with a 40% increase in the readmission rate (from 4% to 5.6%) [23] and others observed an increase in the ER visit rate [24]. Using the Metabolic and Bariatric Surgery Accreditation and Quality Improvement Program data set, Inaba et al found a signi cantly higher morbidity (3.76% vs. 1.54%) and mortality rate (0.94% vs. 0.05%) when comparing same-day discharge to POD1 discharge [25]. Similarly, Morton et al discovered that an LOS of ≤1 day was associated with a signi cantly increased risk of 30-day mortality (OR 2.02) for RYGB patients [26].…”
Section: Discussionmentioning
confidence: 98%
“…Others observed an increase in the ER visit rate as a result of shortening the target LOS [21]. Using the Metabolic and Bariatric Surgery Accreditation and Quality Improvement Program data set, Inaba et al found a signi cantly higher morbidity (3.76% vs. 1.54%) and mortality rate (0.94% vs. 0.05%) when comparing same-day discharge to POD1 discharge after RYGB [22]. In another review from a large prospective database, Morton et al discovered that an LOS of ≤ 1 day was associated with a signi cantly increased risk of 30-day mortality (OR 2.02) and a trend toward an increased risk of serious complications for RYGB patients [23].…”
Section: Discussionmentioning
confidence: 99%
“…The first retrospective study by Morton et al published in 2014 found increased 30-day mortality in patients undergoing RYGB in an ambulatory setting compared to patients who stayed 2 nights (odds ratio: 13.02; P < 0.001). The second study of Inaba et al published in 2018 was based on the large MBSAQIP database (bariatric registry in the USA) comparing 319 patients undergoing primary RYGB with SDD to 9402 patients discharged on postoperative day 1 and also found more complications in the SDD group (1.31% vs. 0.84 %, p <0.001) [ 12 ]. Both previous articles concluded that RYGB without overnight stay is not safe.…”
Section: Discussionmentioning
confidence: 99%
“…However, several small prospective studies assessed SDD after SG using a strict selection of patients did not show increased morbidity and mortality [5][6][7][8][9][10][11]. The only available data about SDD after RYGB is from three retrospective studies with conflicting results regarding feasibility and safety [12][13][14]. To our knowledge, no prospective studies have been performed on the feasibility of SDD after a primary laparoscopic RYGB.…”
Section: Introductionmentioning
confidence: 99%